PERAN SISTEM INFORMASI MANAJEMEN BANK SYARIAH INDONESIA DALAM MEMBANTU PENINGKATAN PEREKONOMIAN DAN BISNIS DI ERA DIGITAL - Julianto Julianto; Reni Helvira (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
Bank Syariah Indonesia is one of the largest state-owned banks whose operations use Islamic sharia principles, which is a combination of three banks, namely Bank Mandiri Syariah, BNI Syariah, and BRI Syariah. This bank has many banking services that can be utilized by customers to help improve, facilitate, and develop every existing business, with many services that can be accessed anytime and anywhere enabling business management to be carried out quickly, effectively, and efficiently. The development and improvement of Information Technology and Sharia Banking Management Information Systems have made mobile and internet banking superior products and services that are very helpful in supporting customer activities related to financial transactions. With technological devices that allow fellow BSI bank officers to enter into each other, share data, and become a pioneer in increasing the use of Islamic banks, namely the development of Islamic banks always increases every year, this indicates that customer interest in banking is very high. The purpose of this study is to describe the development of the role of the Indonesian Sharia Bank Management Information System in helping to improve the economy and business in the digital era. This study uses a qualitative approach using data collection techniques to study literature.